Pay (No) Attention to the Man Behind the Curtain: The Effects of Revealing Institutional Affiliation in a Consortial Chat Service - Barrett, Kathryn; Pagotto, Sabina (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2021)
This study aims to understand how users within a library consortium perceive chat service provided by staff members who are unaffiliated with the user’s home library. The researchers examined 293 chat interactions from Ask a Librarian, a consortial virtual reference service provided to university libraries across Ontario, Canada. Chi-square tests of independence were performed to explore the relationship between user dissatisfaction and instances where the chat operator revealed a mismatch in institutional affiliation between the operator and the user. Moderating variables in the relationship were investigated, including user type, question type, and operator behaviors like transferring the chat, making a referral, revealing a lack of expertise, and saying no to the patron. The researchers found that when an operator revealed that they work at a different institution than the user, patrons are more likely to be dissatisfied if they are graduate students, if their question is research-related, if the operator does not offer to transfer the chat, and if the operator does not state that they lack expertise on the chat topic. These findings suggest that chat operators should be mindful of context and relationships when revealing information about their affiliation. Users may perceive operators from other institutions as lacking knowledge about their local library, or they may be confused or alienated when receiving “behind the scenes” information about staffing that they perceive as unnecessary. The researchers recommend emphasizing and strengthening the user’s relationship with their home library and local library staff.